The role of social networks in the inclusion of small-scale producers in agri-food developing clusters. (May 2018) - Ramirez, Matias; Bernal, Paloma; Clarke, Ian; Hernandez, Ivan
Highlights: Network theory is used to explain patterns of connectivity in agribusiness. The discussion is framed through a typology of inclusion of small producers. Local social capital dynamics significant impact different forms of inclusion. Use of mixed methods can explain relationship between networks and social capital. Abstract: This paper discusses how network theory and social capital can help explain different patterns of inclusion of small and medium sized producers in agri-food clusters. We make the argument that despite the centralized nature of practices, the manner in which inclusion takes place can vary significantly depending on structural features of local networks and governance factors, especially social capital and the role of lead organisations. Social network analysis allows us to investigate how different patterns of bonding, bridging and centrality of key actors in agricultural clusters can influence diffusion of knowledge. We frame this discussion through a typology that allows us to identify diverse scenarios of inclusion of small producers. This is then used to guide an empirical analysis of two agri-food clusters of small producers in Peru (mango) and Colombia (palm oil). Judicious use of mixed methods and the typology can prove useful to explain diverse patterns of inclusion which have important implications for small-scale agricultural producers.